Indirect effects of childhood pneumococcal conjugate vaccination on invasive pneumococcal disease: a systematic review and meta-analysis - Shiri, T; Datta, S; Madan, J; Tsertsvadze, A; Royle, P; Keeling, M; McCarthy, N; Petrou, S (Elsevier, 2017)
Background The full extent to which childhood pneumococcal conjugate vaccines (PCV) can indirectly reduce illness in unvaccinated populations is not known. We aimed to estimate the magnitude and timing of indirect effects of PCVs on invasive pneumococcal disease. Methods In this systematic review and meta-analysis, we searched bibliographic databases for non-randomised quasi-experimental or observational studies reporting invasive pneumococcal disease changes following PCV introduction in unvaccinated populations (studies published Sept 1, 2010, to Jan 6, 2016), updating the previous systematic review of the same topic (studies published Jan 1, 1994, to Sept 30, 2010). Two reviewers extracted summary data by consensus. We used a Bayesian mixed-effects model to account for between-study heterogeneity to estimate temporal indirect effects by pooling of invasive pneumococcal disease changes by serotype and serogroup. Findings Data were extracted from 70 studies included in the previous review and 172 additional studies, covering 27 high-income and seven middle-income countries. The predicted mean times to attaining a 90% reduction in invasive pneumococcal disease were 8.9 years (95% credible interval [CrI] 7.8-10.3) for grouped serotypes contained in the seven-valent PCV (PCV7), and 9.5 years (6.1-16.6) for the grouped six additional serotypes contained in the 13-valent PCV (PCV13) but not in PCV7. Disease due to grouped serotypes contained in the 23-valent pneumococcal polysaccharide vaccine (PPV23) decreased at similar rates per year in adults aged 19-64 years (relative risk [RR] 0.85, 95% CrI 0.75-0.95) and 65 years and older (0.87, 0.84-0.90). However, we noted no changes in either group in invasive pneumococcal disease caused by the additional 11 serotypes covered by PPV23 but not PCV13. Interpretation Population childhood PCV programmes will lead, on average, to substantial protection across the whole population within a decade. This large indirect protection should be considered when assessing vaccination of older age groups. Funding Policy Research Programme of the Department of Health, England.